Frequency, Risk Factors, and Adverse Fetomaternal Outcomes of Placenta Previa in Northern Tanzania - Elizabeth Eliet Senkoro; Amasha H. Mwanamsangu; Fransisca Seraphin Chuwa; Sia Emmanuel Msuya; Oresta Peter Mnali; Benjamin G. Brown; Michael Johnson Mahande (Journal of Pregnancy)
Background and Objective. Placenta previa (PP) is a potential risk factor for obstetric hemorrhage, which is a major cause of fetomaternal morbidity and mortality in developing countries. This study aimed to determine frequency, risk factors, and adverse fetomaternal outcomes of placenta previa in Northern Tanzania. Methodology. A retrospective cohort study was conducted using maternally-linked data from Kilimanjaro Christian Medical Centre birth registry spanning 2000 to 2015. All women who gave birth to singleton infants were studied. Adjusted odds ratios (ORs) with 95% confidence intervals for risk factors and adverse fetomaternal outcomes associated with PP were estimated in multivariable logistic regression models. Result. A total of 47,686 singleton deliveries were analyzed. Of these, the frequency of PP was 0.6%. Notable significant risk factors for PP included gynecological diseases, alcohol consumption during pregnancy, malpresentation, and gravidity ≥5. Adverse maternal outcomes were postpartum haemorrhage, antepartum haemorrhage, and Caesarean delivery. PP increased odds of fetal Malpresentation and early neonatal death. Conclusion. The prevalence of PP was comparable to that found in past research. Multiple independent risk factors were identified. PP was found to have associations with several adverse fetomaternal outcomes. Early identification of women at risk of PP may help clinicians prevent such complications.